Perceptions of family on hospital in intensive environment - Vagner Ferreira do Nascimento, Monique Maira Maciel, Alisséia Guimarães Lemes, Angélica Pereira Borges, Ana Cláudia Pereira Terças, Thalise Yuri Hattori (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v4i2.3402